Associated Factors of Adulthood Overweight/Obesity among Pharmacy Department Students in Al-Rafidain university College / Iraq - Samer Shukur Mohammed1 , Wael Waleed Mustafa2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Youth people overweight or obesity has become a main public health concern globally because of itsadversarial health outcome and escalating prevalence. The aspects of disease conditions demonstrated duringearly older life commonly originate in youth stage of life. Iraq after wars is went through a transition wherethey started to go under-nutrition and co- exists with obesity. even though, there is a lack in documentedinformation on college life and being overweight or obesity in Iraq. our study was carried out to documentedfor the first time the prevalence and associated factors of adulthood overweight or obesity among pharmacydepartment student in Alrafidain university college. Data were collected using a structured self-administeredquestionnaire from February 2019 to December 2019in grades 1–5 students of pharmacy department inAlrafidain university collegeHeight and weight measurements of 300 students were taken and BMI- for-age-sex was calculated usingWHO AnthroPlus. Based on that, participants were divided to three groups as normal weight (BMI 20–25),overweight (BMI 26.0–30), and obese (BMI > 31.0).Participates response rate is 81%. Age of students take a part in the current study was 21.43 ± 3.81 years. Thecategory of students were 96 students (32%) overweight student 90(30%). The significant different P<0.05among groups were found of particular questions included eating outside their home.